FEW POST-LARVAL STAGES AND JUVENILES OF THE SARDINE, SiRDISELLA DAYI REGAN - Bensam, P (Indian Journal of Fisheries, 2011)
Sardinella dayi contributes to a minor extent to the sardine fishery of theTuticorin area in the Gulf of Mannar. A few post-larval stages of this species in the sizerange of 1870mnj.—20.25 mm and juveniles of 28 mm—36 mm are described. Thefood of the post-larvae consisted mainly of copepods. A discussion on the identity ofthe larvae and juveniles as those of S. dayi is given based on circumstancial evidenceand characteristic features distinguishing them from similar stages of related species.